From microvasculature to fibroblasts: Contribution of anti-endothelial cell antibodies in systemic sclerosis. (March 2015) - Corallo, C; Franci, B; Lucani, B; Montella, A; Chirico, C; Gonnelli, S; Nuti, R; Giordano, N
Systemic sclerosis (SSc) is an autoimmune disease characterized by skin and internal organ fibrosis, caused by microvascular dysfunction. In recent years, the hypothesis that anti-endothelial cell antibodies (AECA) play a key role in microvascular damage seems to be increasingly convincing. In fact, AECA can induce antibody-dependent cellular apoptosis and stimulate the microvasculature to release pro-inflammatory and pro-fibrotic cytokines. Human-microvascular-endothelial-cells (MVECs) were stimulated with SSc sera (with and without AECA) and with sera from healthy donors. The conditioned MVEC culture media were then added to fibroblast cultures obtained from control skin (CTR), non-affected skin of SSc patients (NA), and affected skin of the same sclerodermic (SSc) patients, respectively. AECA contributed to the MVEC increased release of endothelin-1 (ET-1) in the culture medium and to MVEC apoptosis. Fibroblast (CTR, NA, and SSc) proliferation was increased after treatment with AECA-positive conditioned media, compared to AECA-negative and control conditioned media. Furthermore, both AECA-positive (in major contribution) and AECA-negative conditioned media were responsible for alpha-smooth-muscle-actin (αSMA) over-expression in all fibroblast cultures, compared to control conditioned media. Fibroblast type I collagen synthesis was upregulated by both SSc conditioned media (with and without AECA). Finally, the synthesis of fibroblast transforming-growth-factor-beta (TGF-β) was statistically higher in AECA-positive conditioned media, compared to AECA-negative and control conditioned media. These findings support the concept that AECA may mediate the crosstalk between endothelial damage and dermal-fibroblast activation in SSc.